Factors that influence the IPO as an exit strategy for private equity investors in the UK. - Upegui, Juan Carlos (2020)
This research paper is focused on determining the factors that influence the decision of an Initial public offering as the main exit strategy for private equity investors in the UK. For this purpose, qualitative and quantitative approaches have been analyzed as it has been stated that the decision of going public does not depend on quantitative reasons only. The information and stake sharing, the cost of the process, and the required company structure harm private investors when considering going public. On the other hand, the reputational profit and a lower cost of debt to carry out future projects have been exposed as positive factors from the qualitative perspective. On the quantitative side, the industry effect through the market performance has been proofed to be significant as explanatory factors for the decision to float into the market. This research analyses the industry's effect on the IPOs for the first time (according to the literature) through five industry market performance indexes. Considering a data set from 2006 and 2019 of the Alternative Investment Market, it has been shown using a Vector Autoregressive model (VAR) that in the short run, the market performance by industry and the previous money raised in IPO exercises Granger-causes the frequency of IPOs. However, macroeconomic variables such as inflation, the 10 years British bond rate of return did not show evidence of a causal relationship with the number of IPOs. The results show a causal relationship with the market volatility and the IPO frequency given by the volatility index in the London Stock Exchange main market. Finally, the impulse and response test over the significant causal variables illustrated negative and positive effects on the IPO frequency by sector which deserves special attention.